Trading in Soweto - De Montille, Sandra (Department of Environmental and Geographical Science, 2016)
The present study aims to examine the history, role and functions of trading in Soweto. The study documents the development of black trading in South Africa from the turn of the century to the mid-1980s. The imposition of increasingly restrictive legislation and negative attitudes towards black trading through the mid-1970s led to the development of small-scale, illegal trading operations, especially hawking. During the 1980s the restrictive legislation was relaxed and attempts, both legislative and financial were made to foster black business. The contemporary structure, form and functions of Soweto as an entity, and as part of metropolitan Johannesburg, are outlined. This is used as a backdrop to the discussion of the legislative constraints and case study analysis of trading in Soweto. The literature review examines the contributions of both the diffusionist paradigm and its offshoot, reformism, as well as various strands of the Marxist paradigm to studies of trading in Third World situations. The chapter then turns to an alternative construct, structuration, as a framework within which to place the study of trading in Soweto. The core of the study is a case study of trading in Soweto. To this end both traders and consumers are scrutinized and traders are ranked along a continuum from petty traders, small-scale and of ten illegal and mobile; to large-scale, formal, sanctioned traders. To carry out this analysis four areas were selected from the townships of Soweto, in pairs of contrasting socio-economic levels, and with two of the areas containing nodal concentrations of shops. The areas are Diepkloof, Dube, Moletsane and Pimville. Questionnaire interviews were conducted with consumers selected by systematic sampling of houses in the pre-selected areas, with traders operating from formal business premises, who were identified through the consumer survey and through fieldwork. The case study profiles the characteristics of formal 'and petty traders and investigates the differences in character between food, clothing and alcohol traders. Next is an investigation of the traders in Soweto in the context of metropolitan Johannesburg. An attempt to determine the degree to which petty traders are functional or alternatively dysfunctional to capital (i.e., formal enterprises) is undertaken. The theory of structuration is explored to investigate the actions of actors, namely traders and consumers. Legislative, economic and political institutions are examined as structures which may be both constraining and enabling for these actors under different circumstances. It is concluded that considerable diversity exists among the traders in Soweto and that, although government policy has moved from repression to active support of black businesses, the actual number of "formal" traders in Soweto has declined in recent years. The functionalist argument that petty traders provide low-cost goods which sustain the low wages paid to employees of formal enterprises, is not borne out by the data. It is felt, however, that the State benefits from the existence of petty traders as they ameliorate the need for a well- developed welfare system. Similarly, this group's demonstrated capacity to produce employment opportunities is seen as a survival strategy rather than part of a sustained development of the urban economy. The analysis of the actors in the context of structuration in this study adds an important dimension to research beyond that offered by structural-functionalist accounts of the Marxist paradigm. Future research on trading in Soweto and in other geographical locations may be profitably enhanced by the adoption of a structurationist perspective.